Surface Reconstruction Using Rational Quartic Triangular Spline - Draman, N.N.C. (Springer Science and Business Media B.V., 2021)
Reconstruction a smooth surface from non-uniform points is a major challenge in many areas. This paper discusses C1 surfaceÂ scattered data interpolationÂ using rational quarticÂ triangular patches with two different existing convex combination. In order to achieve C1 continuity, we apply a rational corrected that obtained from convex combinationÂ between three local schemes. To validate our proposed method, we tested the scheme by using two test functions and two real applications from established dataset. We measured the performance by comparing errors which is maximum error, root mean square (RMSE), coefficient of determination (R2) and central processing unit (CPU). All numerical and graphical results are obtained using MATLAB R2019a. From the result, we found that the proposed scheme is better than existing scheme. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.